2015
DOI: 10.1002/2015jc011329
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐ocean mixing due to surface gravity waves

Abstract: Surface gravity waves play an important role in the lower layer of the atmosphere and the upper layer of the ocean. Surface waves effect upper‐ocean mixing mainly through four processes: wave breaking, Stokes drift interaction with the Coriolis force, Langmuir circulation, and stirring by nonbreaking waves. We introduce the impact of these four processes into a 1‐D k−ϵ ocean turbulence model. The parameterizations used are based mainly on existing investigations. Comparison of simulation results and measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 60 publications
2
62
0
2
Order By: Relevance
“…For α this set up is in agreement with most of the studies, where it also is treated as 1.0 [11,14,25]. The empirical constant β ranges between 0.15 and 1.5 by fitting Eq.…”
Section: Model Descriptionsupporting
confidence: 69%
See 1 more Smart Citation
“…For α this set up is in agreement with most of the studies, where it also is treated as 1.0 [11,14,25]. The empirical constant β ranges between 0.15 and 1.5 by fitting Eq.…”
Section: Model Descriptionsupporting
confidence: 69%
“…If the wave spectrum is narrow enough bulk parameters can indeed characterize the effect of the irregular wave motion with sufficient accuracy, as opposed to deriving turbulent mixing and shear production from the spectrum [19]. In the absence of a wave spectrum (modeled or measured), many researchers successfully applied mixing parametrizations based on bulk characteristic [14,23] but it has to be underlined that several studies reported that model results improve significantly by using a 2D spectral wave model since wave mixing can be overestimated by bulk parametrizations [25,26].…”
Section: Model Descriptionmentioning
confidence: 99%
“…It should be noted that Langmuir cells (with a length scale of ∼5–100 m) cannot be resolved with this horizontal resolution. Incorporating the impact of Langmuir cells on the ocean mixing requires an additional parameterization [ Wu et al ., ], which is a topic of future studies. There are 40 sigma levels in the vertical which are concentrated near the surface and bottom, and are equally distributed in the interior.…”
Section: The Coupled Wave‐circulation Modelmentioning
confidence: 99%
“…[] also showed that mesoscale eddies can be detected from the synthetic aperture radar images via the influence of eddy currents on the surface wave fields. In the ocean upper layer, the Coriolis‐Stokes force, Langmuir circulation, breaking, and nonbreaking wave‐induced mixing all contribute to the upper ocean mixing [ Wu et al ., ]. For example, Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The experimental settings of the control experiment Exp_NW are same as those of the Exp‐1 in Wu et al . [], except that the vertical resolution is set to 0.2 m in this study. For details of the parameters for experiments Exp_NW and Exp_1, refer to Wu et al .…”
Section: Resultsmentioning
confidence: 99%